Racism & racial discrimination in Malaysia : a historical & class perspective / by Kua Kia Soong - Kua, Kia Soong (SUARAM, 2015)
This book is about the politics of race and class in Malaysia, highlighting the structural conditions that enable the crude manipulation of race to serve the economic interests of the ruling elite. The chapters on the Emergency contain declassified documents from the British Public Records Office, which were made available after the 30-year secrecy rule was lifted. The author offers alternatives that are needs-based and thus race-free by doing away with such discriminatory policies, rent-seeking activities and patronage politics.